Near-field phase shift photolithography for high-frequency SAW transducers - Hesjedal, T; Seidel, W; Kostial, H (2002)
Optical lithography has been widely used in mass production of various electronic devices, mainly because of its high throughput capability. However, the resolution in conventional lithography is diffraction limited. Cost issues, on the other hand, make slower but higher resolution methods, like electron beam lithography, unattractive for industrial applications. In order to be able to continue the use of optical lithography, new schemes were developed that enhance the resolution. Phase-shifting masks, for example, alter both the amplitude and the phase of the exposing light and lead to higher resolution. Using the related phase edge method it has been shown that 100 nm features can be produced using 248 nm light. Furthermore, employing an elastomeric phase mask, commercially available photo resist, and incoherent light, down to 90 nm features were demonstrated. Here, we report on the application of a near-field phase shift technique on the fabrication of SAW transducers. This simple and low cost technique is best suited for the fabrication of SAW structures, where the metallization ratio is different from 1:1, like Narrow Gap Floating Electrode Unidirectional Transducers (NG-FEUDTS).